Pontos quânticos de carbono aplicados ao sensoriamento químico de íons cobalto e metilcobalamina - Oliveira, Carlos Mateus Paiva (2024)
Carbon Quantum Dots (CQDs) constitute a class of fluorescent nanoparticles, generally less than 10 nm in size, with biocompatible properties and low toxicity. They exhibit a structure enriched with hydrophilic functional groups on the surface, ensuring high dispersibility in aqueous media. Due to these properties, CQDs emerge as promising nanomaterials for applications in chemical sensing, utilizing fluorescence emission as a detection mechanism. The aim of this study was to use CQDs for the sensing of Co²⁺ ions and the methylcobalamin (MC) molecule. The CQDs were synthesized by the hydrother- mal method using citric acid, ethylenediamine, and mercaptosuccinic acid (MSA) as pre- cursors. This method allowed for the production of selective nanoparticles with better control of functionalization. The CQD samples exhibited two absorption bands, charac- teristic of π-π* and n-π* electronic transitions, with a quantum yield of 8%. The CQDs had an average size of 4.3 ± 1.55 nm and displayed emission bands at 450 nm, regardless of the excitation wavelength. After optimizing the experimental conditions, including the influence of pH, the effect of potential interferents, and optimized concentrations of CQDs, titration curves for Co²⁺ and MC were constructed. The efficient fluorescence quenching of CQDs related to Co²⁺ ions and MC was used for analyte detection, resulting in a detection strategy with a limit of detection (LOD) of 0.86 mmol L-1 and 1.016 μmol L-1 for Co²⁺ and MC, respectively, indicating a high sensitivity of the detection platform, as the LOD values are below the maximum limit for Co²⁺ and MC established by the WHO for drinking water samples. Subsequently, Co²⁺ ions and MC were identified in a real sample of tap water, using standards obtained by Linear Discriminant Analysis (LDA). With a 95% confidence level, the sensor was able to distinguish the analytes in the real sample. The recovery results showed a recovery range between 95% and 105%. Therefore, it was possible to develop a CQD-based sensing approach for the detection and quantification of Co²⁺ ions and MC.